Reducing the risk of stroke in elderly patients with non-valvular atrial fibrillation: a practical guide for clinicians - Foody JM (Dove Medical Press, 2017)
Joanne M Foody Department of Medicine, Harvard Medical School, Boston, MA, USA Abstract: Non-valvular atrial fibrillation (NVAF) significantly contributes to the burden of stroke, particularly in elderly patients. The challenge of optimizing anticoagulation therapy is balancing efficacy and bleeding risk, especially as the same patients at high risk of stroke also tend to be at high risk of bleeding. Treating the elderly patient with NVAF presents special challenges because of their heightened risk for both stroke and bleeding. Despite clinical trial data and evidence-based guidelines, surveys indicate that physicians underuse anticoagulation in older patients for reasons that include overemphasis of bleeding risk, particularly with the increased risk of falling, at the cost of thromboembolic risk. Clinical trial data are now available, and real-world data are emerging, to illustrate the relative merits of the non-vitamin K antagonist oral anticoagulants compared with conventional anticoagulation in the treatment of elderly patients with this condition, and to suggest some subgroups of older patients who may be more suitable candidates for particular agents. Care of elderly patients with NVAF is often complicated by factors including risk of falling, adherence, health literacy, cognitive function, adverse effects, and involvement of caregivers, as well as other factors including the patient–provider relationship and logistical barriers to obtaining medication. Thus, conversations between clinicians and patients, as well as shared decision making, are important. In addition, elderly patients often suffer from comorbidities including hypertension, coronary heart disease, diabetes mellitus, COPD, and/or heart failure, which necessitate the use of multiple concomitant medications, increasing the risk of drug/drug interactions. This review provides an overview of clinical trial data on the use of non-vitamin K anticoagulant agents in elderly populations, and serves as a practical resource for the management of NVAF in the elderly patient. Keywords: aged, non-vitamin K antagonist oral anticoagulants, stroke, warfarin, bleeding